Citric acid future prospects for Pakistan, a short review - Nadeem, S. (Trans Tech Publications Ltd, 2014)
Considered weak organic acid, Citric Acid (CA) finds its application in almost all the food and pharmaceutical industries as flavour, acidifier and chelating agent. CA has been found in abundance specially in citrus fruits, can also be produced by artificial means, most notably by fermentation using molasses or starch by the use of micro-organisms. The current paper outlines the production of CA from Aspergillus Niger (A. Niger) keeping in view the statistical analysis that shows its importance, usage and future scope of CA if manufactured at industrial scale in Pakistan. Â© 2014 Trans Tech Publications, Switzerland.